Po polsku nie tylko się mówi! Metodyka nauczania kultury w dydaktyce polonistycznej w Chinach - Yinan, Li (Postscriptum Polonistyczne, 2020)
The article presents experiences that result from teaching Polish culture at the Chair of Polish Language at Beijing Foreign Studies University and the author’s idea concerning practical usage of knowledge about Poland during language classes. The author has described methods of teaching Polish culture in Polonistic didactics according to the theory of teaching foreign languages and the differences between Polish and Chinese culture. The article consists of four parts: justification of the necessity of introducing information about Poland, an image of the culture in teaching language skills, popularizing knowledge about Poland and recapitulation. This description is of scientific and analytical character.